2018
DOI: 10.1007/s10545-018-0201-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of amino acid neurotransmitters: the synaptic disorder underlying inherited metabolic diseases

Abstract: Amino acids are involved in various metabolic pathways and some of them also act as neurotransmitters. Since biosynthesis of L-glutamate and γ-aminobutyric acid (GABA) requires 2-oxoglutarate while 3-phosphoglycerate is the precursor of L-glycine and D-serine, evolutionary selection of these amino acid neurotransmitters might have been driven by their capacity to provide important information about the glycolytic pathway and Krebs cycle. Synthesis and recycling of amino acid neurotransmitters as well as compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…Gln is then shuttled back to presynaptic GABAergic neurons via glutamine transporter SLC38A3 (SN1) and glutamine transporter SLC38A2 (GLNT). In SSADH-D, SSA cannot be converted to succinate but is reduced to GHB by SSA reductase (SSAR) (adapted from [15,16]).…”
Section: Metabolitementioning
confidence: 99%
“…Gln is then shuttled back to presynaptic GABAergic neurons via glutamine transporter SLC38A3 (SN1) and glutamine transporter SLC38A2 (GLNT). In SSADH-D, SSA cannot be converted to succinate but is reduced to GHB by SSA reductase (SSAR) (adapted from [15,16]).…”
Section: Metabolitementioning
confidence: 99%
“…In addition, using multi-tissue metabolomics analysis, we previously revealed that the levels of glutamate and glutamine were significantly reduced in the kidney of male mice during T1D development, but not in female mice [34] . Aspartate and glycine are two major amino acid neurotransmitters in multiple brain regions [56] and serve as a selective agonist for N-methyl- d -aspartate (NMDA) receptors, which has also been associated with cognitive functions [57] . Relative to female mice, we detected a higher level of aspartate in the midbrain and higher glycine in the cortex, striatum and cerebellum in male mice.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 Increased cerebral Phe competes with Gly and Glu for their receptors, changing the levels of receptor expression and thus influencing the synaptic function. 16 A previous study reported that the glutamatergic synaptic transmission in the brain is impaired in patients with PKU. 17 PKU patients have reduced myelin formation and dopamine levels.…”
Section: Introductionmentioning
confidence: 99%
“…In PKU, elevated plasma Phe levels impair the transport of other LNAAs, resulting in cerebral depletion of LNAA and hence decreased biosynthesis of protein and impaired brain function . Increased cerebral Phe competes with Gly and Glu for their receptors, changing the levels of receptor expression and thus influencing the synaptic function . A previous study reported that the glutamatergic synaptic transmission in the brain is impaired in patients with PKU .…”
Section: Introductionmentioning
confidence: 99%